Os Donos de São Benedito: convenções e rebeldias na luta entre o catolicismo tradicional e devocional na cultura de Bragança, século XX - SILVA, Dario Benedito Rodrigues Nonato da (Universidade Federal do Pará, 2013)
This dissertation discusses images and representations found in Literature and conflicts for the cultural control in the Commemoration, the Fraternity and the Marujada of Saint Benedict, in the city of Bragança, state of Para, in the Brazilian Amazon, since the thirtieth decade, in the 20th century. Analyzing a wide bibliography of the themes Folklore, Memory, Popular Tradition and Anthropology, the study attempts to explain how the social relations were built between the historic personages of the Catholic church through the Prelazia do Guamá and the Fraternity of Glorious Saint Benedict of Bragança, in relation to literary vision and the main theorists of historiography, to understand the official e popular Catholicism in their representations, as in the symbols made in time, as historical elements in fights between ideals and rules of the ecclesiastic catholic control and the popular reaction against it of the brothers of Saint Benedict.